Immobilization of lipase in ordered mesoporous materials: Effect of textural and structural parameters - Serra, Elías; Mayoral, Álvaro; Sakamoto, Yasuhiro; Blanco Martín, Rosa María; Díaz Carretero, Isabel (Microporous and Mesoporous Materials, 2008)
A systematic study dealing with the influence of several parameters on the immobilization of lipase in ordered mesoporous materials (OMM) is presented here. In a first step, a series of OMM have been synthesized trying to cover the most relevant structures. The aim is to get variation in the key properties susceptible of influencing their behavior as lipase supports, such as the structure (cubic or hexagonal), the nature of the pores (channel-like or cage-like), the connectivity of the porous network and the pore size. Also, by following the co-condensation technique, 5–10%-methylated analogues of the pure-silica materials have been prepared. All the samples have been fully characterized with XRD, TEM (including 3D reconstruction), SEM, TGA and N2 isotherms, and the incorporation of the organic function has been demonstrated by 29Si NMR. All of them have been tested as supports in the immobilization of Candida antarctica Lipase B (CaLB) and the leaching of the enzyme in aqueous media evaluated. With such a systematic approach, valuable information on the influence of the textural properties and the nature of the porous network on the yields of immobilization and enzyme desorption have been stated. Very interestingly, leaching of the enzyme can be diminished until it practically disappears without being covalently bonded to the wall, which places the ordered mesoporous materials at the starting point of a new scenario in enzyme immobilization on preexisting supports. Financial support for this work was obtained from project CAM (GR/MAT/0694/2004). We thank D. Ramiro Martínez (Novozymes Spain) for his kind help with the supply of CaLB, Silica PQ for supplying the amorphous silica SA and BASF for gently donating the Pluronics. E. Serra acknowledges Comunidad de Madrid for a PhD fellowship. We also thank Dr. T. Blasco for obtaining the 29Si NMR spectra and Dr. R. García for the SEM analyses. YS thanks Swedish Research Council (VR) for financial support. Peer reviewed